Surface and Underground Magnetic Investigations in the Southern Coalfields of New South Wales (The Australasian Institute of Mining and Metallurgy, 1967)
Magnetic anomalies in the Southern Coalfields have been subdivided into two characteristic types. Each type is attributed to a separate cause, one being basement structure, and the other near-surface igneous intrusions.Detailed geological mapping of the area and the ability to sample throughout the coalmines greatly assisted in this subdivision.The Triassic sequence contributes no magnetic effect of its own except to diminish the effect of sources within the underlying formations by raising the level of observation.Detecting the presence of igneous intrusions ahead of colliery working faces by magnetic observations within the coal mines may be of value in preventing accidents caused by gas outbursts and in planning the workings so as to avoid loss of production time.